Effects of at-work exercises on computer operators. - Kietrys DM; Galper JS; Verno V (Work, 2007)
At-work exercises are commonly recommended for computer operators. This randomized control trial assessed adherence, pain and satisfaction after 4 weeks of at-work exercise. Subjects (n=72) were randomized into 3 groups: resistance exercise, stretching, and control. Outcomes included a satisfaction survey, a visual analogue pain scale (VAS), a pain drawing, and the Neck Disability Index (NDI). The VAS, the drawing, and NDI were analyzed together as a composite variate referred to as Pain Impact. Exercise frequency was similar across the 3 groups (median=1.5 times per day). No differences were found between groups on Pain Impact p=0.714) or individual pain variables. Most satisfaction survey item scores did not differ between groups. However, a significant difference between groups on the survey item related to discomfort. The resistance and stretching group differed from the control group with regard to their perception that the exercises were helpful in reducing discomfort in the back and neck (p<0.001). We conclude that most subjects found the resistance and the stretching exercises easy to do, performed them 1 to 2 times daily, and said they reduced discomfort. To determine optimal type and frequency of at-work exercises, further study is needed.